Bosman as Verbindingsteken: Hybridities in the Writing of Herman Charles Bosman. - Leff, Carol Willa (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2014)
This thesis is concerned with how hybridity is created and interpreted by Herman Charles Bosman in his fiction and non-fiction. Bosman was a gifted writer and raconteur who captured the historical, socio-political context of his time by translating Afrikaans culture for the edification and pleasure of an English readership. Hennie Aucamp summed up this linguistic and cultural translation by pointing out that Bosman was a writer who acted as a "verbindingsteken" or hyphen (65) between Afrikaans and English. His texts contain many voices, and are therefore essentially hybrid. Firstly, by drawing on aspects of postcolonial theory, the terms 'hybridity', 'culture' and 'identity', are discussed. Homi Bhabha's notion of 'hybridity' is the conceptual lens through which Bosman's texts are viewed, and aspects of Mikhail Bakhtin's cultural theory also serve the same function. Thereafter, biographies of Bosman are discussed in an effort to understand his hyphenated identity. Following this, specific attention is paid to a selection of Bosman's essays, short stories, and a novel. Scholarly opinions aid interpretation of levels of hybridity in Bosman's work. In analysing Bosman's texts critically, it becomes clear that he believed in a united South Africa that acknowledged and accepted all races. However, analysis also reveals that there are some inconsistencies in Bosman's personal views, as expressed particularly in his essays. His short stories do not contain the same contradictions. Critical analysis of the novel Willemsdorp attests that cultural hybridity is not always viewed as celebratory. It can also be a painful space where identities are split, living both inside and outside their environment, and subsequently marginalized. Bosman's texts, although published decades ago, remain relevant today in post-apartheid South Africa as much of his writing can be seen as a record of historical events. His short stories and novels capture a confluence of languages, people and cultures. His essays illustrate a deep commitment to promoting South African culture and literature. When reading Bosman one is constantly reminded that differences are not only to be acknowledged, but embraced, in what he prophetically imagined as a hybrid, post-apartheid South African society.
Keywords: Bosman, Herman Charles, 1905-1951 -- Criticism and interpretation; South African fiction (English) -- 20th century -- History and criticism; Authors, -- South African -- 20th century; South Africa -- Social life and customs -- 20th century; National characteristics, -- South African